Development and experimental evaluation of a complete solar thermophotovoltaic system. (4th April 2012) - Datas, Alejandro; Algora, Carlos
ABSTRACT We present a practical implementation of a solar thermophotovoltaic (TPV) system. The system presented in this paper comprises a sunlight concentrator system, a cylindrical cup‐shaped absorber/emitter (made of tungsten coated with HfO2), and an hexagonal‐shaped water‐cooled TPV generator comprising 24 germanium TPV cells, which is surrounding the cylindrical absorber/emitter. This paper focuses on the development of shingled TPV cell arrays, the characterization of the sunlight concentrator system, the estimation of the temperature achieved by the cylindrical emitters operated under concentrated sunlight, and the evaluation of the full system performance under real outdoor irradiance conditions. From the system characterization, we have measured short‐circuit current densities up to 0.95 A/cm2, electric power densities of 67 mW/cm2, and a global conversion efficiency of about 0.8%. To our knowledge, this is the first overall solar‐to‐electricity efficiency reported for a complete solar thermophotovoltaic system. The very low efficiency is mainly due to the overheating of the cells (up to 120 °C) and to the high optical concentrator losses, which prevent the achievement of the optimum emitter temperature. The loss analysis shows that by improving both aspects, efficiencies above 5% could be achievable in the very short term and efficiencies above 10% could be achieved with further improvements. Copyright © 2012 John Wiley & Sons, Ltd.